On communication in a divided society. - H.C. Marais (Communicare)
ON July 2nd 1985 the Human Sciences Re- search Council released its main report on intergroup relations in South Africa, The South African Society: Realities and Future Prospects. This paper provides an overview of this investigation with specific reference to the role of communication in intergroup relations. The background to this study is first discussed, followed by some of the more salient conclusions contained in the main report. Specific issues concerning communication and intergroup relations are dealt with in conclusion